Efektivitas Bantuan Transportasi Laut Masyarakat Desa Numbing Kecamatan Bintan Pesisir - Mandala, Edward; A. Karim, Zamzami; Setyadiharja, Rendra; Usman Siam, Nurbaiti; Wahyu Lumintu, Cyntia (STISIPOL Raja Haji, 2024)
The Bintan Regency Government provides transportation assistance to the people of Numbing Village so that it can be used to make it easier for people to carry out activities between islands. In practice, the use of government-assisted ferries is still not efficient due to various obstacles, namely lack of members and inadequate operating hours. The aim of this research is to determine the effectiveness of sea transportation for the Numbing village community so that sea transportation becomes more effective and efficient. The research method used is qualitative with a qualitative descriptive approach. Data collection techniques were carried out using observation, interviews and documentation methods. The samples in this research were the Head of the Infrastructure Division of the Bintan Regency Transportation Service, the Head of the Finance Program of the Bintan Regency Transportation Service, the Numbing Village Secretary, the ship's captain, and the community. Primary data uses interview techniques with secondary data in the form of documentation, journals, books and field observations. From the results of this research, it can be concluded that assistance for sea transportation for the community of Numbiing Village, Bintan Pesisir District, can be said to be effective, if seen from the provision of ship assistance. However, the factualization that occurs in the field can be considered less effective. This is due to the lack of operational hours maintained by ship managers, so that people still find it difficult to enjoy the sea transportation provided.